The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.arr.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

RNA surveillance—An emerging role for RNA regulatory networks in aging

Abstract: In this review, we describe recent advances in the field of RNA regulatory biology and relate these advances to aging science. We introduce a new term, RNA surveillance, an RNA regulatory process that is conserved in metazoans, and describe how RNA surveillance represents molecular cross-talk between two emerging RNA regulatory systems – RNA interference and RNA editing. We discuss how RNA surveillance mechanisms influence mRNA and microRNA expression and activity during lifespan. Additionally, we summarize re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…Moreover, certain single nucleotide polymorphisms at ADAR gene loci are associated with exceptional longevity in humans; in Caenorhabditis elegans , interactions between the RNA editing machinery and ncRNA regulatory networks are partly responsible for regulating lifespan [56, 57]. These observations link brain aging and longevity with ncRNA circuitry and implicate these relationships in determining age-related cognitive changes and disease onset.…”
Section: Life Cycles and Molecular Functions Of Non-coding Rnasmentioning
confidence: 99%
“…Moreover, certain single nucleotide polymorphisms at ADAR gene loci are associated with exceptional longevity in humans; in Caenorhabditis elegans , interactions between the RNA editing machinery and ncRNA regulatory networks are partly responsible for regulating lifespan [56, 57]. These observations link brain aging and longevity with ncRNA circuitry and implicate these relationships in determining age-related cognitive changes and disease onset.…”
Section: Life Cycles and Molecular Functions Of Non-coding Rnasmentioning
confidence: 99%
“…It is possible that the truncated protein that we found in our aging rats might be the one where there is loss of catalytic activity. RNA editing is compromised during aging [26]. In humans, several single nucleotide polymorphisms in the RNA editing genes ADARB1 and ADARB2 were seen in extremely old age in a US-based study on centenarians.…”
Section: Discussionmentioning
confidence: 99%
“…Mature miRNAs can also undergo ADAR-mediated editing [ 25 ]. Earlier studies have shown that RNA editing is compromised during aging [ 26 , 27 ]. There is currently not much known about how adipomiRs are regulated during aging, a knowledge of which will help understand the role of these non-coding RNAs in metabolic diseases associated with aging.…”
Section: Introductionmentioning
confidence: 99%
“…In depth analysis of RNA-seq data will allow the identification and study of emerging modulators of aging such as regulatory ncRNAs described in section 3.2.5 (reviewed in (Montano and Long, 2011)). Reproducibility of RNA-seq will also facilitate compilation of different studies to increase sample number and statistical significance.…”
Section: System-level Analysis Of Retinal Agingmentioning
confidence: 99%